Judicial Review on The Application of Criminal Offense of Evil Conspiracy to Narcotic Drug Courier Based on Act Number 35 Year 2009 about Narcotics (Verdict of District Court of Medan Number 1537/Pid.Sus/ 2015/PN.MDN) - Khairun Na’im (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Evil conspiracy/samenspanning is a criminal action, on the other word, the crime is the agreed, prepared, or planned criminal action, which has not been yet happened (inchoate). In Criminal Code Guideline (hereafter KUHP), trying of criminal action and evil conspiracy are punished lightly from the actual punishment. However, it is different from current narcoticsdrug Act that gives the same punishment with the actual punishment on completed offense. It is due to the consideration that narcotic crime has become serious crimes. It turns out that according to Narcotics Drug Act, the applicable article of evil conspiracy is also limited. The consideration of evil conspiration as one of criminal offense may be caused by criminal action of narcotics as stated in Narcotic Drug Act Number 35 Year 2009as an extraordinary crime particularly for young generation.The issues rise in the application of legal process in proving the crime of evil conspiracy. It is due to the difficulty in finding the evidences of the crimes. For instance, what the evidences are that can be considered if evil conspiracy happened in doing the narcotic drug crime.